Mini suction probe for matric suction measurements - Meilani, Inge (2011)
A modified triaxial apparatus with mini suction probes was fabricated to study the matric suction along the specimen height during unsaturated triaxial testing. Three mini suction probes were placed at 3/4, 1/2, and 1/4 height of the specimen, each at 120° apart in the lateral direction. This paper presents the development of the mini probe for matric suction measurements. Evaluation of the performance shows that the fabricated mini probe provides a rapid response and accurate reading under negative and positive pore-water pressure changes. Matric suctions as high as 400 kPa were successfully measured on soil specimens over a time span of 15 h. On the other hand, the mini suction probes were also found to be able to measure a matric suction of 200 kPa for a longer period of 155 h.